2002
DOI: 10.2139/ssrn.328900
|View full text |Cite
|
Sign up to set email alerts
|

Open Source Projects as Horizontal Innovation Networks - By and For Users

Abstract: Innovation development, production, distribution and consumption networks can be built up horizontally -with actors consisting only of innovation users (more precisely, "user/self-manufacturers"). "Free" and "open source" software projects are examples of such networks, and examples can be found in the case of physical products as well.User innovation networks can function entirely independently of manufacturers when (1) at least some users have sufficient incentive to innovate, (2) at least some users have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 36 publications
0
20
0
8
Order By: Relevance
“…In both the industrial and consumer goods fields, customers, or more generally users, are often found to be the initial developers of products, prototypes, and processes which later gain commercial significance (Von Hippel, 2002). Furthermore, studies have demonstrated that up to 30% of users surveyed report that they have developed a new product for personal or in-house use (Von Hippel, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In both the industrial and consumer goods fields, customers, or more generally users, are often found to be the initial developers of products, prototypes, and processes which later gain commercial significance (Von Hippel, 2002). Furthermore, studies have demonstrated that up to 30% of users surveyed report that they have developed a new product for personal or in-house use (Von Hippel, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Need information is very complex, and conventional market research techniques only skim the surface. Deeper techniques, such as ethnographic studies, are both difficult and time-consuming (von Hippel, 2001). Therefore, they have instead equipped customers with tools to design and develop their own products (toolkits), ranging from minor modifications to major innovations (Thomke and von Hippel, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Authors have treated openness as willingness to use knowledge/ideas from customers, orther organizations, R and D institutions, suppliers/vendors etc., outside the firm (West, Salterb, Vanhaverbekec, and Chesbrough 2014;Chesbrough 2003Chesbrough , 2006Chesbrough , 2011Urban and von Hippel 1988;von Hippel 2002von Hippel , 2005Von Hippel et al 2011;Dahlander and Gann 2010;Baldwin and von Hippel 2011;De jong et al 2008;De Wit et al 2007;Hyo et al 2016). Yun et al (2010), and Yun and Avvari 2012;Bughin, Chui and Johnson, 2008;Gassman and Enkel, 2004;Immelt, Govindrajan and Trimble, 2009;Govindrajan and Trimble, 2012;West and Bogers, 2014;Pansera, 2013;Di Minin, Frattini, and Piccaluga 2010.…”
Section: Part Imentioning
confidence: 99%